2014
DOI: 10.17221/164/2014-cjgpb
|View full text |Cite
|
Sign up to set email alerts
|

Genetic analysis and molecular mapping of leaf rust resistance genes in the wheat line 5R618

Abstract: Wang J., Shi L., Zhu L., Li X., Liu D. (2014): Genetic analysis and molecular mapping of leaf rust resistance genes in the wheat line 5R618. Czech J. Genet. Plant Breed., 50: 262-267.The wheat (Triticum aestivum L.) line 5R618, bred at the China Agricultural University, is resistant in the seedling stage to the majority of the current Chinese pathotypes of wheat leaf rust (Puccinia triticina). To identify and map the leaf rust resistance gene in the 5R618 line, F 2 plants and F 2:3 families from a cross betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…The percentage of other genes were as Lr26 and Lr35 (93%), Lr39 (66%), Lr37 (53%), Lr19 (33.3%) and Lr46 (26.6%). Wang et al (2014) reported that wheat line 5R618, F2 plants and F2:3 families from a cross between 5R618 and Zhengzhou5389 (susceptible) may contain Lr9, Lr24, Lr19, Lr28, Lr39, Lr42, Lr47, Lr51, and Lr53 genes using molecular markers. Vanzetti et al (2011) studied 66 wheat cultivars from Argentina to identify Lr genes that condition leaf rust resistance.…”
Section: Discussionmentioning
confidence: 99%
“…The percentage of other genes were as Lr26 and Lr35 (93%), Lr39 (66%), Lr37 (53%), Lr19 (33.3%) and Lr46 (26.6%). Wang et al (2014) reported that wheat line 5R618, F2 plants and F2:3 families from a cross between 5R618 and Zhengzhou5389 (susceptible) may contain Lr9, Lr24, Lr19, Lr28, Lr39, Lr42, Lr47, Lr51, and Lr53 genes using molecular markers. Vanzetti et al (2011) studied 66 wheat cultivars from Argentina to identify Lr genes that condition leaf rust resistance.…”
Section: Discussionmentioning
confidence: 99%
“…Barakat et al (2010) developed F2 mapping population in maize (Zea mays L.) and identified ISSR makers linked to northern corn leaf blight resistance Ht1 gene. Wang et al (2014) identified and mapped the leaf rust resistance gene in wheat line 5R618 by using F2 mapping population and F2:3 families between 5R618 and the susceptible wheat 'Zhengzhou 5389'. Takagi et al (2013) identified QTLs for partial resistance to rice blast disease and seedling vigour in recombinant inbred lines and F2 populations of rice using QTL-seq.…”
Section: Introductionmentioning
confidence: 99%
“…Markers that are polymorphic between the pools might be genetically linked to the loci determining the trait (Wang et al. , Qi et al. ).…”
mentioning
confidence: 99%
“…resistant and susceptible for a particular disease), are analysed to identify markers that distinguish them. Markers that are polymorphic between the pools might be genetically linked to the loci determining the trait (Wang et al 2014, Qi et al 2015. In the present experiment, an attempt was made to identify genetic resources resistant to dry root rot, understand the genetics and to detect SSR markers putatively linked to genomic region/s conferring dry root rot resistance through bulked segregation analysis.…”
mentioning
confidence: 99%
See 1 more Smart Citation